Monitoring the agri-food system in Myanmar: Rice millers – June 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand the effects of recent economic and political disruptions on Myanmar’s rice sector, we conducted an additional round of a telephone survey of medium- and large-scale rice millers in June 2021.